Ethical values and competitiveness within concentrated ownership structure in Malaysia / Mohd Farhan Mohd Dah … [et al.] - Mohd Dah, Mohd Farhan; Zainon, Saunah; Zakaria, Nor Balkish; Omar, Normah (Universiti Teknologi MARA Cawangan Selangor, 2016)
Ethical values of business are normally jeopardized by the stiff competitions among them. Thus, ownership structure plays vital roles to balance these issues. This paper aims to study the relationship between ownership structures and performance pre and post Malaysian Codes on Corporate Governance (MCCG) 2012 revision. Based on a random sampling of 100 Bursa Malaysia listed companies, a final of 500 firm-year observations were chosen for the duration of 2010 till 2014. This study engaged several univariate and multivariate analyses to serve the empirical evidence. Despite the better Corporate Governance practices among the sample companies, the multivariate results showed that family ownership, government ownership, institutional ownership and company size have significant and positive relationship with firm performance only for MCCG 2012 revision. Due to the unfavorable Malaysian stock market for both 2013 and 2014, the results of post MCCG 2012 revision showed an insignificant effect between ownership structures and firm performance. Even though the corporate governance practices were favorably reported, the ownership structures were still powerless to influence the firm performance.